ECOSOPHY ADVICE IN TUNJUK AJAR MELAYU: A CRITICAL ECOLINGUISTIC STUDY - Fauzi, Mohd; Amelia, Vita; Islami, Qori; Syam, Essy (Annual International Conferences on Language, Literature, and Media, 2022)
This article describes the ecosophy of the advice of environmental preservation found in Tunjuk Ajar Melayu (Malay teachings) texts compiled by Tennas Effendy (2014). It applies documentation method to collect the data. The collected data are then analyzed using critical ecolinguistics proposed by Arran Stibbe and local wisdom concept by Sibarani. The results show that there are four main kinds of environmental aspects pertaining human responsibility to the environment in the  texts discussed, (1) protecting the universe, (2) managing the universe wisely, (3) preserving the nature, and (4) passing down the nature to the future generations. From the texts studied, it is found that there is a close relationship between humans and their environment, the relationship between humans and other humans, and the relationship between humans and their God. The 71 expressions studied from Malay teaching and learning texts, all reveal Malay local wisdom whose aim is to preserve their environment, because they know that if the forest, sea, river, and lake environments are destroyed, the structure of Malay society and Malay customs will also be lost.